Sarah's choice [large type] - Brunstetter, Wanda E. (Brunstetter, Wanda E. Brides of Lehigh Canal, 2010)
Widowed Sarah Turner has her hands full, raising three young children, tending the lock on the canal, baking bread, and washing clothes for boatmen. Although she's not looking for love, she's vowed not to lose her heart to a boatman. Yet she didn't count on meeting Captain Elias Brooks. Will she follow her heart where it leads or accept the proposal of a handsome land-loving blacksmith?